Informatization Construction of Digital Assets in Smart Cities. (22nd October 2021) - Ning, Wenze; Lu, Mei
Abstract : With the rapid popularization of the Internet of Things (IoT), smart cities driven by IoT technology have become a matter of concern. This study mainly investigates the construction of digital asset based on the data collected from government departments, enterprises and institutions. Particularly digital asset personnel should not only get familiar with the process of smart city information management, but also be able to identify the risks in digital assets. Strict accountability mechanism can ensure the data privacy, dispel the worries of data providers, and help weaken data barriers. Supported by comprehensive numerical results, we reach a conclusion that our proposed digital asset construction scheme has practical significance in many aspects of smart city development and will help the regional Informatization considerably.